Estudo do comportamento da sinterização de compactos de cavacos de um aço SAE 1050 obtidos sob alta pressão - Resende, Leonardo (2014)
From an economic standpoint, the powder metallurgy (P/M) is a technique widely used for the production of small parts. It is possible, through the P/M and prior comminution of solid waste such as ferrous chips, produce highly dense sintered parts and of interest to the automotive, electronics and aerospace industries. However, without prior comminution the chip, the production of bodies with a density equal to theoretical density by conventional sintering techniques require the use of additives or significantly higher temperatures than 1250ºC. An alternative route to the production of sintered bodies with high density compaction from ferrous chips (≤ 850 microns) and solid phase sintering is a compression technique under high pressure (HP). In this work, different compaction pressures to produce a sintered chip of SAE 1050 carbon steel were used. Specifically, the objective was to investigate them, the effect of high pressure compression in the behavior of densification of the sintered samples. Therefore, samples of the chips from the SAE 1050 carbon steel were uniaxially cold compacted at 500 and 2000 MPa, respectively. The green compacts obtained were sintered under carbon atmosphere at 1100 and 1200°C for 90 minutes. The heating rate used was 20°C/min. The starting materials and the sintered bodies were characterized by optical microscopy, SEM, XRD, density measurements (geometric: mass/volume, and pycnometry) and microhardness measurements Vickers and Rockwell hardness. The results showed that the compact produced under 2000 MPa presented relative density values between 93% and 100% of theoretical density and microhardness between 150 HV and 180 HV, respectively. In contrast, compressed under 500 MPa showed a very heterogeneous microstructure, density value below 80% of theoretical density and structural conditions of inadequate specimens for carrying out the hardness and microhardness measurements. The results indicate that use of the high pressure of ferrous chips compression is a promising route to improve the sinterability conditions of this type of material, because in addition to promoting greater compression of the starting material, the external tension acts together with surface tension, functioning as the motive power for sintering process. Additionally, extremely high pressures allow plastic deformation of the material, providing an intimate and extended contact of the particles and eliminating cracks and pores. This tends to reduce the time and / or temperature required for good sintering, avoiding excessive grain growth without the use of additives. Moreover, higher pressures lead to fracture the grains in fragile or ductile materials highly hardened, which provides a starting powder for sintering, thinner, without the risk of contamination present when previous methods are used comminution of the powder.